Concordant Intestinal Atresia in Two Pairs of Monozygotic Twins - Giuffrè, Mario; Catania, Mariavalentina; Corsello, Giovanni (American Journal of Perinatology Reports, 2011)
Intestinal atresia in both twins from the same pregnancy is very rare. Only seven pairs of twins have been described. The authors report on two cases of monozygotic twins with different types of intestinal atresia and clinical evolution. Both pairs of observed twins turned out to be concordant for the presence of intestinal malformations and for the absence of other linked malformations; nevertheless, the atresic lesions were anatomically discordant in each pair of monozygotic twins. Therefore, the diagnostic and therapeutic procedures have shown some differences in phenotypic expression between the twins of both pairs. Possible etiologic factors and pathogenetic pathways are discussed, and the importance of an accurate clinical and instrumental investigation and a long-term follow-up is underlined. Very rare models, such as pairs of monozygotic twins presenting intestinal atresia, represent an extraordinary resource to add new clinical and laboratory information likely to be useful in future advancements to understand the underlying etiology and pathogenesis.
Keywords: Intestinal atresia; monozygotic twins; apple peel; double-bubble sign; malformation; concordance